2015
DOI: 10.1002/prot.24871
|View full text |Cite
|
Sign up to set email alerts
|

Protein structure refinement via molecular‐dynamics simulations: What works and what does not?

Abstract: Protein structure refinement during CASP11 by the Feig group is described. Molecular dynamics simulations were used in combination with an improved selection and averaging protocol. On average, modest refinement was achieved with some targets improved significantly. Analysis of the CASP submission from our group focused on refinement success vs. amount of sampling, refinement of different secondary structure elements and whether refinement varied as a function of which group provided initial models. The refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 39 publications
8
113
1
Order By: Relevance
“…We already discussed that the new iterative protocol mostly outperformed the more conservative protocol employed in previous rounds of CASP, with additional improvements when both protocols were combined. Simply in terms of numbers, our performance during CASP13 was also better than during CASP12.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We already discussed that the new iterative protocol mostly outperformed the more conservative protocol employed in previous rounds of CASP, with additional improvements when both protocols were combined. Simply in terms of numbers, our performance during CASP13 was also better than during CASP12.…”
Section: Resultsmentioning
confidence: 91%
“…The approach has been adopted as part of many structure prediction protocols as an endgame player in structure prediction . This approach improved for a few years due to advances in force fields and benefited from an ability to carry out longer simulations . However, there was little progress in recent years even with much longer simulations .…”
Section: Introductionmentioning
confidence: 99%
“…58 In these cases, enhanced sampling, as performed in our study, is necessary. Moreover, CASP11 results demonstrated that loops tend to be more challenging to refine.…”
Section: Discussionmentioning
confidence: 89%
“…Structure prediction relying on knowledge-based approaches seems to have reached a plateau in their accuracy, 58 and different refinement strategies are now required to achieve effective improvements. The combination of knowledge-based prediction with physics-based methods looks particularly promising.…”
Section: Discussionmentioning
confidence: 99%
“…These regions correspond predominantly to loops, insertions of any length, and non-conserved side chains. The most significant part of comparative modeling termed as model or loop refinement is done using either of techniques, fragment-guided molecular dynamic simulation (FG-MD) [19], GalaxyRefine [20,21], 3Drefine [22][23][24], protein structure refinement via molecular dynamics (PREFMD) [25], Errat-guided LM via MODELLER [7] and molecular dynamics simulations (MDS) via AMBER16 [26] However, none of them describes the effectiveness of one method over the other in terms of model validation parameters, required experimental time and tediousness of each method during refinement procedure. Identifying the most effective technique can help in selecting the best refinement method, possibly reducing the required computational time and accelerate the process for refinement of homology model.…”
Section: Mtr Homology Model Refinement Using Mdsmentioning
confidence: 99%